Utilization of transitional care management services and 30-day readmission - Kim, Eun Ji; Coppa, Kevin; Abrahams, Sara; Hanchate, Amresh D.; Mohan, Sumit; Lesser, Martin; Hirsch, Jamie S. (PloS one, 2025)
Transitional care management (TCM) visits have been shown to reduce 30-day readmissions, but it is unclear whether the decrease arises from the TCM visit itself or from clinic-level changes to meet the requirements of the TCM visits. We conducted a cross-sectional analysis using data from Northwell Health to examine the association between the type of post-discharge follow-up visits (TCM visits versus non-TCM visits based on billing) and 30-day readmission. Furthermore, we assessed whether being seen by a provider who frequently utilizes TCM visits or the TCM visit itself was associated with 30-day readmission. We included adult patients hospitalized to Medicine service and subsequent follow-up visits within two weeks of discharge between February 24, 2018, and February 24, 2020. We examined 1) post-discharge follow-up visit type (TCM visit versus non-TCM visit) and 2) provider characteristics (frequent TCM visit utilization or not). The primary outcome was unplanned hospital readmission within 30 days following hospital discharge. After propensity matching, TCM follow-up visits were associated with decreased 30-day readmissions (hazard ratio = 0.74 [0.63–0.88]) compared to non-TCM visits. Among patients with non-TCM follow-up visits, those seen by a provider who frequently used TCM visits had decreased odds (OR = 0.84 [0.71–0.99]) of 30-day readmission compared to those seen by providers who did not use TCM visits regularly. Among patients who followed up with providers who frequently use TCM visits, TCM visits were associated with decreased 30-day readmission compared to patients with non-TCM visits (OR = 0.78 [0.62–0.98]). The study has limitations, including the health system database not capturing all out-of-network follow-up visits. The reduction in 30-day readmission associated with TCM visits likely arises from both the visit itself and being seen by a provider who frequently uses TCM visits.